Let f(x)=4x+2 and g(x)=3x^2+3x. After simplifying, (f@g)(x)=?

Globokim8 2021-01-25 Answered
Let f(x)=4x+2 and g(x)=3x2+3x.
After simplifying, (fg)(x)=?
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

ottcomn
Answered 2021-01-26 Author has 97 answers
Compute the composite function as,
fg(x)=f(g(x))
=f(3x2+3x)
4(3x2+3x)+2
=12x2+12x+2
Hence, the composite function fg(x) is,
fg(x)=12x2+12x+2
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more